Cardiovascular responses of three salmonid species affected with amoebic gill disease (AGD) - Leef, MJ; Harris, J; Hill, JV; Powell, MD (Journal of Comparative Physiology B, 2005)
The cardiovascular effects of amoebic gill disease (AGD) were investigated immediately following surgery in three salmonid species; Atlantic salmon (Salmo salar L.), brown trout (Salmo trutta L.) and rainbow trout (Oncorhynchus mykiss Walbaum). Fish, both nave (control) and infected (AGD-affected) of each species, were fitted with dorsal aorta catheters and cardiac flow probes. Cardiac output and dorsal aortic pressures were then continuously measured over a 6-h period following surgery. Results showed that Atlantic salmon, brown trout and rainbow trout displayed similar dorsal aortic pressure, cardiac output, and systemic vascular resistance (mean dorsal aotic pressure divided by cardiac output) values. However, the only significant differences relating to disease status i.e. infected or control, were found in Atlantic salmon. Although no significant differences were seen in dorsal aortic pressure values, AGD-affected salmon displayed significantly elevated systemic vascular resistance at 4 and 6 h post surgery. Cardiac output was also approximately 35% lower in AGD-affected salmon compared to the non-affected control counterparts. These results comparatively examine cardiac function in response to AGD across three salmonid species and highlight species-specific cardiovascular responses that occur in association with disease. It is suggested that the apparent cardiac dysfunction seen in AGD-affected Atlantic salmon could, under stressful conditions, become exacerbated. Cardiac failure is therefore suggested to be a possible physiological mechanism by which AGD causes or contributes to mortality in Atlantic salmon. Springer-Verlag 2005.